A Pan-Cancer Analysis of SMARCA4 Alterations in Human Cancers - Peng, Ling; Li, Jisheng; Wu, Jie; Xu, Bin; Wang, Zhiqiang; Giamas, Georgios; Stebbing, Justin; Yu, Zhentao (Frontiers in Immunology, 2021)
Background: SMARCA4,the essential ATPase subunit of SWI/SNF chromatin remodeling complex, regulates transcription through the control of chromatin structure and is increasingly thought to play significant roles in human cancers. This study aims to explore the potential role of SMARCA4 with a view to providing insights on pathologic mechanisms implicated here. Methods: The potential roles of SMARCA4 in different tumors were explored based on The Cancer Genome Atlas (TCGA), Genotype-tissue expression (GTEx), Tumor Immune Estimation Resource (TIMER), and Gene Set Enrichment Analysis (GSEA) datasets. The expression difference, mutation and phosphorylation status, survival, pathological stage, DNA methylation, tumor mutation burden (TMB), microsatellite instability (MSI), mismatch repair (MMR), tumor microenvironment (TME), and immune cell infiltration related to SMARCA4 were analyzed. Results: High expression levels of SMARCA4 were observed in most cancer types. SMARCA4 expression in tumor samples correlates with poor overall survival in several cancers. Lung adenocarcinoma cases with altered SMARCA4 showed a poorer prognosis. Enhanced phosphorylation levels of S613, S695, S699 and S1417 were observed in several tumors, including breast cancer. SMARCA4 correlated with tumor immunity and associated with different immune cells and genes in different cancer types. TMB, MSI, MMR and DNA methylation correlated with SMARCA4 dysregulation in cancers. SMARCA4 expression was negatively associated with CD8+ T cell inﬁltration in several tumors. Further, the SWI/SNF superfamily-type complex and ATPase complex may be involved in the functional mechanisms of SMARCA4, albeit these data require further confirmation. Conclusions: Our study offers a comprehensive understanding of the oncogenic roles of SMARCA4 across different tumors. SMARCA4 may correlate with tumor immunity.